Optimization of micronutrient supplement for enhancing biogas production from food waste in two-phase thermophilic anaerobic digestion - Menon, Ajay (2017)
The aim of this study was to enhance the biogas productivity of two-phase thermophilic anaerobic digestion (AD) using food waste (FW) as the primary substrate. The influence of adding four trace metals (Ca, Mg, Co, and Ni) as micronutrient supplement in the methanogenic phase of the thermophilic system was investigated. Initially, Response Surface Methodology (RSM) was applied to determine the optimal concentration of micronutrients in batch experiments. The results showed that optimal concentrations of 303, 777, 7 and 3 mg/L of Ca, Mg, Co and Ni, respectively, increased the biogas productivity as much as 50% and significantly reduced the processing time. The formulated supplement was tested in continuous two-phase thermophilic AD system with regard to process stability and productivity. It was found that a destabilized thermophilic AD process encountering high VFA accumulation recovered in less than two weeks, while the biogas production was improved by 40% yielding 0.46 L CH4/gVSadded/day. There was also a major increase in soluble COD utilization upon the addition of micronutrient supplement. The results of this study indicate that a micronutrient supplement containing Ca, Mg, Co and Ni could probably remedy any type of thermophilic AD process.